Experimental investigation of compound-specific dilution of solute plumes in saturated porous media: 2-D vs. 3-D flow-through systems - Ye, Yu; Chiogna, Gabriele; Cirpka, Olaf; Grathwohl, Peter; Rolle, Massimo (Journal of Contaminant Hydrology, 2015)
Dilution of solute plumes in groundwater strongly depends on transverse mixing. Thus, the correct parameterization of transverse dispersion is of critical importance for the quantitative description of solute transport. In this study we perform flow-through laboratory experiments to investigate the influence of transport dimensionality on transverse mixing. We present a high-resolution experimental setup to study solute dilution and transverse dispersion in three-dimensional porous media. We conduct multi-tracer experiments in the new 3-D setup and compare the results with the outcomes of analogous tracer experiments performed in a quasi 2-D system. We work under steady-state flow and transport conditions and consider a range of velocities relevant for groundwater flow (0.5-8 m/day). Transverse dispersion coefficients are determined from high-resolution concentration profiles at the outlet of the flow-through chambers (7 × 7 ports in the 3-D setup and 7 ports in the quasi 2-D system), considering conservative tracers with significantly different aqueous diffusion coefficients, namely fluorescein and dissolved oxygen. To quantify dilution in the 2-D and 3-D systems, we experimentally determine the flux-related dilution index using the flow rates and the concentrations measured at the inlet and outlet ports, and we propose semi-analytical expressions to predict its evolution with travel distance in uniform groundwater flow. The experimental results in the quasi 2-D and 3-D flow-through systems are consistent and show a compound-specific behavior of the transverse dispersion coefficient and its non-linear dependence on the seepage velocity in both setups. The degree of dilution and the compound-specific effects of transverse dispersion are considerably more pronounced in 3-D than in quasi 2-D transport systems.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Dilution; Flux-related dilution index; Laboratory experiments; Mixing; Transverse dispersion